2012
DOI: 10.1159/000343774
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Temperature Gradient Is Increased in Eyes with Bacterial Corneal Ulcers

Abstract: Aims: To investigate the ocular surface temperature gradient in eyes with bacterial corneal ulcers. Methods: Prospective examination of 12 eyes with bacterial corneal ulcers (group 1) and 12 control eyes (group 2). Infrared thermal imaging (Tomey TG 1000) was used to study the temperature of the ocular surface. The mean, minimum and maximum temperature of the ocular surface and temperature course over a time period of 10 s of sustained eye opening were evaluated. Furthermore, a correlation between the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
(12 reference statements)
0
16
0
1
Order By: Relevance
“…Earlier, using a totally different experimental approach we demonstrated that the T 1/2 of meibum was about 32 °C, with approximately 90% of meibum melted at 35 °C (Butovich et al, 2010). In recent studies, the mean eyelid temperature in healthy people with no ocular disorders was measured to be between 30.7 ± 1.2 °C (Pult et al, 2012), 32.2 ± 0.8 °C (Shih et al, 2010) and 33.4 ± 0.1 °C (Nagymihalyi et al, 2004), the mean corneal surface temperature was between 31.7 ± 0.9 °C (Shih et al, 2010), 32.3 ± 0.5 °C (Terada et al, 2004), and 34.8 ± 0.8 °C (Efron et al, 1989; Klamann et al, 2013). All these temperatures are falling between the T m values of human meibum (~30 °C) and its effective completion temperature of transition (~35.5 ± 0.5 °C).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, using a totally different experimental approach we demonstrated that the T 1/2 of meibum was about 32 °C, with approximately 90% of meibum melted at 35 °C (Butovich et al, 2010). In recent studies, the mean eyelid temperature in healthy people with no ocular disorders was measured to be between 30.7 ± 1.2 °C (Pult et al, 2012), 32.2 ± 0.8 °C (Shih et al, 2010) and 33.4 ± 0.1 °C (Nagymihalyi et al, 2004), the mean corneal surface temperature was between 31.7 ± 0.9 °C (Shih et al, 2010), 32.3 ± 0.5 °C (Terada et al, 2004), and 34.8 ± 0.8 °C (Efron et al, 1989; Klamann et al, 2013). All these temperatures are falling between the T m values of human meibum (~30 °C) and its effective completion temperature of transition (~35.5 ± 0.5 °C).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover it has been pointed out that temperature of nasal limbus tends to be higher than other regions of eye because of increased blood flow [10] . In this study, we also noticed lower central cornea temperature than nasal limbus, but we did not collect the temperature from the central cornea which had lower temperatures than body core temperature [12] . Our temperature results obtained from carancula lacrimalis region correspond with rectal and tympanic temperatures.…”
Section: Discussionmentioning
confidence: 63%
“…Thermography does not have the benefit of knowing the signal source, because it is [180] 2013 2a 1 ---Arita et al [181] 2013 2a 1 ---Purslow [182] 2013 1a 1 ---Klamann et al [183] 2013 2a 1 ---Petznick et al [184] 2013 2a 1 ---Gonnermann et al [178] 2012 2a 1 ---Kottaiyan et al [185] 2012 2a 1 ---Tan et al [186] 2011 4a 1 ---Kamao et al [187] 2011 2a 2 -83 80 Tan et al [188] 2010 4a 1 ---Tan et al [189] 2010 3a 1 ---Tan et al [190] 2010 2a 1 ---Acharya et al [191] 2009 4a 1 ---Chiang et al [192] 2006 2a 2 -79.3 75 Purslow et al [193] 2005 2a 2 ---Cherkas et al [194] 2003 2a 1 ---Morgan et al [195] 1999 1a ----Mori et al [196] 1997 1a 1 ---Morgan et al [197] 1996 2a 1 ---Morgan et al [198] 1995 2a 1 --- Table 6: Pain and inflammation diagnosis results. Authors Year MP PE A (%) Se (%) Sp (%) Jeong et al [203] 2013 2b ----Dibai Filho et al [204] 2013 1b 1 ---Kang et al [202] 2013 2b ----Rodrigues-Bigaton et al [88] 2013 1a 2 -62.2 75.6 Dibai Filho et al [205] 2013 1a 2 60 55.8 55.8 Zaproudina et al [206] 2013 2a 1 ---Roy et al [207] 2013 2a 1 ---Choi et al [201] 2013 2b 1 ---Zaproudina et al [208] 2013 2a 1 ---Frize and Ogungbemile [209] 2012 3b 3 -96 92 Hildebrandt et al [210] 2012 2b ----Laino [211] 2012 2b ----Wu et al [212] 2009 2b 1 ---Chang et al [213] 2008 1b 1 ---Niehof et al [214] 2007 2a 2 -74.3 83.9 Park et al …”
Section: Discussionmentioning
confidence: 99%